GAMBARAN STRES KERJA PADA PEKERJA OPERATOR DUMPTRUCK PT. X KOTA TARAKAN KALIMANTAN UTARA: Description of Work Stress on Dumptruck Operator Workers Pt. X Tarakan City, North Kalimantan - Sigit Hendriawan Eko Permadi; Muhamad Hasim Dwi Prajitno (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2018)
ABSTRACK Dumptruck operators have a risk of experiencing job stress. The aim of this research is to describe the level of work stress and analyze the related factors with the occurrence of work stress on dumptruck operators in PT Mandiri Intiperkasa Tarakan City. This research is a qualitative research was an descriptive observational design. The respondents was a 110 dump truck operators used simple random sampling method. Data ware collection used Generic Job Stress Questioner from NIOSH for job stress and questionnaires Depression Anxiety Stress Scale 42 (DASS 42) that has been modified to determine stress level and data analysis used Spearmen correlation test. The results of this study showed that from 110 respondents there are had very low job stress level with 73 people (66,4%), had low job stress with 23 people (20,9%) and had moderate job stress of 14 people (12, 7%). There were a correlation betwen lenght of work (p= 0,000),, interpersonal conflict(p= 0,000),, job uncertainty(p= 0,009),, employment Opportunity (p= 0,000), work demands (p=0,003) mental demands (p=0,000). But there were no correlation between Age (p= 0,115), , marital status (p= 0,381), and role conflict (p=0,071) with job stres. The conclusion of this research is the level of job stress dumptruck operator PT. Mandiri Inti Perkasa tends to be low and still within normal limits so as not to disrupted its work performance.